2020
DOI: 10.1177/1055665620923925
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Speech, Velopharyngeal Function Outcomes and Surgical Characteristics Following the Sommerlad Protocol and Palate Repair Technique

Abstract: Objective: To report speech and velopharyngeal function (VPF) outcomes, and surgical characteristics, at age 5 following early complete palate closure using the Sommerlad protocol. Design: A retrospective, descriptive, cross-sectional consecutive series. Setting: A regional twin site center; a district general hospital and tertiary children’s hospital. Participants: Between 1993 and 2006, 877 participants underwent surgery; 712 (81%) were eligible for inclusion; 391 (55%) were included, 321 (45%) excluded. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 133 publications
(220 reference statements)
7
42
2
Order By: Relevance
“…A comparable (or lower) percentage of children with non-oral CMAs have been reported in other countries/languages as well in recent years (Ainoda et al, 1985; Park et al, 2000; Persson et al, 2006; Albustanji et al, 2014: Baillie & Sell, 2020; Hortis-Dzierzbicka et al, 2014; Klinto et al, 2014; Sell et al, 2015; Willadsen et al, 2017; Nyberg et al, 2018). Sell and colleagues (2015) reported speech outcomes for 248 five-year-old children in the Cleft Care UK study and noted that only 10% produced non-oral CMAs.…”
Section: How Many Children Produce Them?supporting
confidence: 78%
See 1 more Smart Citation
“…A comparable (or lower) percentage of children with non-oral CMAs have been reported in other countries/languages as well in recent years (Ainoda et al, 1985; Park et al, 2000; Persson et al, 2006; Albustanji et al, 2014: Baillie & Sell, 2020; Hortis-Dzierzbicka et al, 2014; Klinto et al, 2014; Sell et al, 2015; Willadsen et al, 2017; Nyberg et al, 2018). Sell and colleagues (2015) reported speech outcomes for 248 five-year-old children in the Cleft Care UK study and noted that only 10% produced non-oral CMAs.…”
Section: How Many Children Produce Them?supporting
confidence: 78%
“…Although a high percentage of substitutions seen in these children were attributed to glottal stops and pharyngeal fricatives in the early 1960s (Spriestersbach et al, 1961; Westlake & Rutherford, 1966), several authors were reporting a decrease in the frequency of these atypical substitutions even at that time (Morley, 1962; Renfrew, 1968). The number of children who produce CMAs has declined over the years and that observation has been attributed, at least in part, to the earlier age that palatal surgery is being performed as well as early intervention (Ysunza et al, 1998; Hardin-Jones & Jones, 2005; Peterson-Falzone et al, 2010; Baillie & Sell, 2020).…”
Section: How Many Children Produce Them?mentioning
confidence: 99%
“…It is likely that speech-language therapy intervention was similar across both groups but we do not know if there were differences in the speech-language therapy intervention they received. Information on the quantity and quality of speech-language therapy intervention has been noted to be difficult to obtain in other studies (Baillie and Sell, 2020). Lack of this information means it is not possible to know how speech-language therapy intervention may have had an impact on the results at any of the assessment time points.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral cleft lip and palate (BCLP) is rare, making up approximately 10% of the overall cleft population (Cleft Registry and Audit Network, 2019), and in many studies that have reported speech development and speech outcomes in children with cleft palate, children with BCLP were excluded (Lohmander, 2011). Where children with BCLP have been included in such studies (Hardin-Jones and Jones, 2005; Sullivan et al, 2009; Mahoney et al, 2013; Choa et al, 2014; Klintö et al, 2018; Baillie and Sell, 2020) they have consistently presented with less favorable speech outcomes and more surgical complications. According to the Cleft Registry and Audit Network (2019), only 36.2% of children with BCLP were rated to have “normal speech” at age 5 years (Cleft Registry and Audit Network, 2019), compared to 73.6% of children with isolated cleft palate.…”
Section: Introductionmentioning
confidence: 99%
“…Factors specific to children with a cleft palate include the type of cleft, width of cleft, and palatal length. Interventional factors can impact speech outcome and include timing and technique of surgical repair, surgeon experience, volume of procedures, and the availability of routine multidisciplinary cleft palate team care (Mahoney et al, 2013;Golinko et al, 2016;Wu et al, 2017;Baillie & Sell, 2020).…”
Section: Introductionmentioning
confidence: 99%